(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Salmonellosis is a significant public health concern around the world. The issue of antibiotic resistance, particularly in non-typhoidal Salmonella (NTS), is a global threat to human and animal health. Thirty-five Salmonella enterica subsp. enterica serotype Typhimurium (S. Typhimurium) isolated from various chicken samples were tested for antimicrobial-resistant profiling using the disc diffusion method. The strains were further examined for the presence of the resistance genes by using polymerase chain reaction (PCR) according to published protocols. Phenotype resistance profiling revealed that 22.9% (8 out of 35) isolates showed resistance to five antibiotics used in this study. All the penta-resistant isolates carried the blaTEM, floR, strA, and tetA gene which encoded for ampicillin, chloramphenicol, streptomycin, and tetracycline resistance. Only one isolate (1 out of 35) was found to contain the sulfonamides resistance, sulA gene. Nine isolates were found susceptible to all antibiotics tested and do not harbor any of the resistant associated genes. These findings provide evidence that the presence of resistance genes contributes to the phenotypic resistance profile, and thus could give rise to the emergence of the drug-resistant strain of Salmonella.